GEOCHEMICAL, PETROGRAPHIC AND PETROPHYSICAL STUDIES TO EVALUATE THE SUITABILITY OF LIMESTONE FOR CEMENT INDUSTRY IN THE OUTCROPS OF FATH'A FORMATION, SUKKARIA AREA, WEST OF BAIJI. - Al-Obaidy, Sfoog (Iraqi Journal of Science, 2024)
The geochemical, petrography, petrophysical, and some mechanical tests were done on the limestone samples of five quarries of Fath'a formation, west of Al-Sukkaria village, to evaluate the Suitability of the limestone as carbonate component in the mixture of cement industry.The results reflect the rising the concentrations of CaO and loss on ignition, and the decrease of the concentrations of SiO2, Al2O3, Fe2O3, SO3, Na2O, K2O, and insoluble residue, According to these geochemical properties, the tested samples are reliable as carbonate component for cement industry. The study of petrography reflect that the main component of the samples is Allochems which represented by Ooids and Pesolites. Digenesis processes, dissolution, micritization and limited recrystalization, were observed in the studied samples. The results of this study were confirmed the results of geochemical, petrophysical and mechanical studies.The petrophysical tests reflect the decrease of total density, specific gravity, and moisture content, and the rising of porosity of the samples. The mechanical tests reflect low compressive strength of the studied samples. These results confirm the suitability of the samples for cement industry.